A novel anthocyanins hydroxyethyl cellulose film for intelligent chicken meat packaging with mechanical study, DFT calculations and molecular docking study - Hebat-Allah S. Tohamy (Scientific Reports)
Abstract This study presents a new type of intelligent food packaging material. The film is created using hydroxyethyl cellulose (HEC) and carbon dots that have been modified with sulfur and nitrogen (S,N–CQDs). These S,N–CQDs are produced from discarded onion peels waste, making the packaging eco-friendly and versatile for food preservation with naked eye response.. The S,N–CQDs within the HEC film (HEC-S,N–CQDs) exhibit remarkable fluorescent change when contact with Salmonella. When applied to chicken meat, the film effectively monitors spoilage by changing color from red to light red. This color change is attributed to the film’s pH sensitivity and its interaction with the increasing pH associated with meat deterioration. The color change which visualized by the naked-eye was an indication of the chicken meat spoilage. These make the film capable of visually detecting changes in food quality, such as spoilage, and inhibiting the growth of foodborne pathogens like Salmonella. Additionally, the antimicrobial properties of S,N–CQDs contribute to extending the shelf life of the packaged meat by 12 days which is more longer than the film without S,N–CQDs (3 days). DFT calculations and decreased the energy gap (0.02664 eV) prove the strong chemical reaction between HEC and S,N–CQDs within the film. The low bond length between the ligand and Salmonella (2.43 A°) compared to the HEC film without S,N–CQDs (2.54 A°) prove the high efficiency of antimicrobial activity for the film which containing S,N–CQDs.